Humor as a source for collaborative storytelling: perspectives on dynamic and static stories - Aerila Juli-Anna; Rönkkö Marja-Leena; Tuula Stenius (De Gruyter Mouton, 2025)
In this article, we investigated a creative learning process aimed at a shared story with humor in a group of 7- and 8-year-olds. In this integrated learning process, children first created an individual drawing and a guided writing assignment on a character that would make others laugh and then placed these characters in a story. The stories were collected via collaborative storytelling and the activity was a problem-solving assignment on a humorous children’s book. The data were analyzed via theory-driven content analysis using Kyriakou and Loizou’s categories of flexibility and originality, as well as the theories of empowerment and the absurd. The results showed that the children preferred scatological humor, which evolved from non-flexible humor to flexible and original humor during the process. The shared stories were divided into static and dynamic stories: static stories presented a solution to the problem, but the humor did not evolve during the collaborative storytelling. The dynamic stories concentrated on the process of problem solving and contained versatile, flexible and original features. It seems that the structure of the creative learning process supported participation and sharing individual perceptions of humor. Further, humor created an engaging starting point for the process and underlines the pedagogical possibilities of humor.